Pharmacological and Other Interventions for Head and Neck Cancer Pain: a Systematic Review - Patrick B. Trotter; Lindsey A. Norton; Ann S. Loo; Jonathan I. Munn; Elena Voge; Kim W. Ah-See; Tatiana V. Macfarlane (Stilus Optimus, 2012)
Objectives: Pain is a common complication in head and neck cancer. The aim of this paper is to evaluate the evidence from randomised control trials investigating pharmacological and non-pharmacological methods of pain management in head and neck cancer. Material and Methods: Medline, Embase and the Cochrane library databases were searched. Squamous cell carcinomas of the head and neck excluding nasopharyngeal and salivary gland cancers were included. The limits were "human" and "randomised clinical trials". A quality assessment was carried out. Results: 13 studies were included with a total of 644 participants. The primary outcome for most of these papers was pain control post-treatment. Levels of bias varied between the studies. Majority (12 out of the 13 studies) reported intervention to be superior to the control or standard therapy in pain management. Only 46% of the studies were carried out on an intention to treat basis. Two studies reported high dropout rates, with one at 66%. Conclusions: There is insufficient evidence from randomised clinical trials to suggest an optimal pharmacological intervention for head and neck cancer pain post-treatment. Further high quality randomised clinical trials should be conducted to develop an optimal management strategy for head and neck cancer pain.